Past and present practices of the Malay food heritage and culture in Malaysia - Abdul Raji, Mohd Nazri; Abdul Karim, Muhammad Shahrim; Che Ishak, Farah Adibah; Arshad, Mohd Mursyid (Elsevier, 2017)
Malay heritage varies from north to south; however, there are various similarities and differences. Essentially, Malay heritage food is influenced by a myriad of cultures, such as Arab, Indian, Chinese, Siamese, Javanese, Minangkabau, and others. Different regions in Malaysia are known for their unique or signature dishes, such as beef rendang, laksa, nasi lemak, and tapai. Indeed, it is noted that Malay food is identical in terms of its spiciness. This can be seen from the prepreparation, methods of cooking, and availability and use of prominent ingredients, such as local aromatic herbs and spices. This article highlights the regional Malay food, past and present practices of Malay food culture, and characteristics of Malay food. In addition, this article also discusses the different occasions and table etiquette practices among Malay communities. The reported findings are expected to contribute to the literature on food culture, specifically in Malay heritage food.